Biopsy-tract haemocoagulase injection reduces major complications after CT-guided percutaneous transthoracic lung biopsy. Issue 9 (September 2022) - Zhou, S.Q.; Luo, F.; Gu, M.; Lu, X.J.; Xu, Y.; Wu, R.N.; Xiong, J.; Ran, X.
Abstract : Aim: To determine whether the injection of haemocoagulase into the biopsy tract can reduce pneumothorax and pulmonary haemorrhage after computed tomography (CT)-guided percutaneous transthoracic lung biopsy (PTLB). Materials and methods: A retrospective study was performed involving patients with undiagnosed pulmonary lesions scheduled for PTLB between January 2020 and March 2021. Patients were assigned to the haemocoagulase group or the non-haemocoagulase group. After CT-guided biopsies were performed with a 17 G coaxial system, patients in the haemocoagulase group received a haemocoagulase injection (0.2–0.5 units) in the biopsy tract as the sheath was withdrawn. Postoperative image studies were performed to evaluate complications, including pneumothorax and pulmonary haemorrhage. Factors, including the patient's position, lesion location, and pathological results, were evaluated to determine their associations with the complications. Results: A total of 100 patients were included, with 44 men and a mean age of 53 years old. The overall incidences of pneumothorax and pulmonary haemorrhage were 15% and 13%, respectively. The incidences of pneumothorax and pulmonary haemorrhage were statistically significantly lower in the haemocoagulase group (8% and 6%, respectively) than in the non-haemocoagulase group (22% and 20%, respectively; p =0.04 and 0.03, respectively). There was no statistically significant difference in haemoptysis between the haemocoagulase (6%) and non-haemocoagulase (2%) groups ( p =0.23). There were also no statistically significant associations of pneumothorax or pulmonary haemorrhage with the patients' positions, lesion location, or pathological results. Conclusion: Biopsy tract haemocoagulase injection reduced the incidences of postoperative pneumothorax and pulmonary haemorrhage after PTLB. Highlights: Biopsy tract haemocoagulase injection reduces pneumothorax and pulmonary haemorrhage. Sealing lung biopsy track can reduce postoperative complications. Sealing lung biopsy track can improve patient safety. Biopsy tract is a factor that potentially increases post-puncture complications.